Eficiência econômica na produção de frangos de corte na região Centro-Oeste: uma análise estocástica - Zilli, Julcemar Bruno; Barros, Geraldo SantAna de Camargo (Revista Gestão da Produção Operações e Sistemas, 2006)
The broiler chicken farming has impressed by its dynamism and competence achieved across the last decades, highlighting Brazil as the second largest world producer. All technological advances have led the country towards the position of one the most efficient producers. However, significant specialization of this activity tends to exclude the minor poultry raisers and the less efficient farmers from the creative and productive process. Thus, this study tried to measure the economic efficiency of broiler chicken farmers in the Brazilian central-western region, by identifying which factors influence on this performance measurement. For this reason, the stochastic profit frontier function in one stage (model 2) was used, in which the border coefficients and the efficiency effects are simultaneously obtained, supposing that the error terms are not identically distributed. The coefficients indicated that a more intense use of family labor could increase the producers profitability. A bigger profit in this activity is being indicated due to the fact that the region is relatively new and due to the existence of favorable conditions for capital and technology investment. Although a continuous tendency associated to the efficiency scale was not observed, there seems to be relevant efficiency gains in the medium and high production scale for the regional standards. Keywords: Economic efficiency; Inefficiency; Stochastic production function; Poultry raising; Rural producers.